A Study on the Falsification of Health Certificates: Perspective of Criminal Law and Professional Ethics - Hartika, Yudia; Saputra, Rio; Pakpahan, Novritsar Hasitongan; Darmawan, Didit; Putra, Arif Rachman (Journal of Social Science Studies, 2023)
The law responsibility of doctors in issuing patient health certificates is an important issue that has a broad impact on community trust and the health system. This research aims to analyze the synchronization of regulations and forms of law responsibility of doctors based on Indonesian legislation. Research uses a normative law method with an analytical and conceptual approach, as well as secondary data from literature and legislation. The results show that vertical synchronization of regulations already exists, however horizontal harmonization still needs to be improved. Doctors’ responsibilities cover civil, criminal, and administrations aspects, with the main challenges in implementation being weak supervision and inconsistent sanctions. To improve the effectiveness of regulations, it is necessary to harmonize rules, provide law education for doctors, and strengthen supervision. As a result, this research contributes to efforts to improve integrity and professionalism in medical practice.